2019
DOI: 10.4187/respcare.07235
|View full text |Cite
|
Sign up to set email alerts
|

The ABCDEF Bundle for the Respiratory Therapist

Abstract: The clinical approach to the critically ill patient has changed dramatically over the last several decades from one of deep sedation to that of mobilizing patients on mechanical ventilation and limiting sedation. The ABCDEF bundle is a multidisciplinary, evidence-based approach to the holistic management of critically ill patients that aims to optimize patient recovery, minimize iatrogenesis, and engage and empower the patient and family during their hospitalization. To achieve this goal, the bundle includes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 101 publications
0
11
0
17
Order By: Relevance
“…Evidences have shown that the awakening trial is necessary for sustaining cortical arousal, which promoted further recovery of the nervous system and improved functional efficiency of the brain ( 36 , 38 ). In addition, as demonstrated in previous research, passive range-of-motion activities (the “E” element) could also stimulate the brain activities that might have contributed to the decrease in the proportion of patient-days with coma ( 39 , 40 ). Further studies are necessary to verify this result.…”
Section: Discussionmentioning
confidence: 69%
“…Evidences have shown that the awakening trial is necessary for sustaining cortical arousal, which promoted further recovery of the nervous system and improved functional efficiency of the brain ( 36 , 38 ). In addition, as demonstrated in previous research, passive range-of-motion activities (the “E” element) could also stimulate the brain activities that might have contributed to the decrease in the proportion of patient-days with coma ( 39 , 40 ). Further studies are necessary to verify this result.…”
Section: Discussionmentioning
confidence: 69%
“…We believe that proof of effectiveness for most of the actions advocated as essential for reversing delirium [1, 7, 8, 14-16] is either no longer required or cannot be assessed unless randomization is applied. On the other hand, there is insufficient information for which medical patients presenting with delirium early M&P is most valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, based on clinical documentation, only a third or less of delirium cases are recognized on admission [7], and delirium screening, particularly outside ICUs, requires considerable improvement. Also, a large number of prevention and management measures have been advocated and validated [14, 15], often grouped under easy-to-remember mnemonics like DELIRIUM [1] or ABCDEF [16]. Unfortunately, once a multidimensional approach has been initiated to address and treat reversible factors, there are almost no measures to improve delirium per se.…”
Section: Introductionmentioning
confidence: 99%
“…The PDC was only calculated for participants who had a minimum of three preventers dispensed on separate occasions in the preceding 12-month period. For the purpose of analysis, adherence was dichotomized to a PDC of 80% or greater (adherent) or a PDC of less than 80% (non-adherent) [ 46 ]. In case no instructions for medication administration appeared in the medication record or in cases where dose variability occurred, standard dosage was used to calculate the number of days covered for each medication dispensed.…”
Section: Methodsmentioning
confidence: 99%